Standardized Extract of Bacopa monniera Attenuates Okadaic Acid Induced Memory Dysfunction in Rats: Effect on Nrf2 Pathway - Dwivedi, Subhash (Hindawi Publishing Corporation, 2013)
The aim of the present study is to investigate the effect of standardized extract of Bacopa monnieri (memory enhancer) and Melatonin (an antioxidant) on nuclear factor erythroid 2 related factor 2 (Nrf2) pathway in Okadaic acid induced memory impaired rats. OKA (200 ng) was administered intracerebroventricularly (ICV) to induce memory impairment in rats. Bacopa monnieri (BM-40 and 80 mg/kg) and Melatonin (20 mg/kg) were administered 1 hr before OKA injection and continued daily up to day 13. Memory functions were assessed by Morris water maze test on days 13–15. Rats were sacrificed for biochemical estimations of oxidative stress, neuroinflammation, apoptosis, and molecular studies of Nrf2, HO1, and GCLC expressions in cerebral cortex and hippocampus brain regions. OKA caused a significant memory deficit with oxidative stress, neuroinflammation, and neuronal loss which was concomitant with attenuated expression of Nrf2, HO1, and GCLC. Treatment with BM and Melatonin significantly improved memory dysfunction in OKA rats as shown by decreased latency time and path length. The treatments also restored Nrf2, HO1, and GCLC expressions and decreased oxidative stress, neuroinflammation, and neuronal loss. Thus strengthening the endogenous defense through Nrf2 modulation plays a key role in the protective effect of BM and Melatonin in OKA induced memory impairment in rats.